Porcupine's Pajama Party - Harshman, Terry Webb; Cushman, Doug (New York : Harper & Row, 1988)
Porcupine bakes cookies, watches a monster movie, and gets scared in the dark when his two best friends sleep over.
Keywords: Friendship -- Fiction